Implementasi Continuous Delivery dengan Zero – Downtime Rolling Update Menggunakan Ansible - Kiki Harapan Hutapea; Muhammad Arif Fadhly Ridha (Jurnal Komputer Terapan, 2022)
Today every organization relies on application to provide services to their customers. In fact, 62% of organizations say application are essential for their business, and a further 36% say application provide a competitive advantage. This makes companies are required to provide innovation quickly in order to give satisfaction and convenience for their customers. To respond these demands, organizations need to deliver application updates more frequently. In the traditional deployment process, each deployment starts with the requirements spesification and ends at production. The weakness of traditional deployment is the slow delivery process, where its done manually and on a step-by-step basis, which can cause points of failure and human errors that resulting in delays or total system shutdowns. Continuous Delivery help organizations speed up the process of delivering applications to customers. One of the software that can build Continuous Delivery with zero-downtime is Ansible. Based on the test, Ansible managed to maintain the service availability with 100% up time rate and able to speed up deployment time by 48%. From load testing, it was found that 1 server was able to handle a load of 2000 users per 5 minutes with 99% success rate.